The Effect of the Method of Practical Presentations to Develop Mental Toughness and Learn Some of Basic Skills for Students in Volleyball - Ayad Nasser Hussein (Journal of Global Pharma Technology, 2016)
The successful teaching helps the learner and the teacher to achieve the planned goals, and depends largely on the good selection of teaching methods that regulate student learning and facilitate them to reach a high degree performing goals of perfection, the teaching methods play an important and fundamental role in the educational situation, and its mastery saves the economy in the time and effort spent, not only that role on the information only, but includes skills, tendencies, trends, thinking methods and others. Through the follow-up of field researchers to teach volleyball in the lesson of physical education, he noted that many of the learners have difficulty in learning basic skills as a result of their teaching methods, and that their teaching needs other methods that lead to the best possible learning in accordance with the development of the game And as appropriate to stimulate the learners' motivation towards learning, and thus reflected on the upgrading of this game and the objective of research to:The preparation of a program in a way practical presentations in the development of mental toughness and learn the basic skills for the students in volleyball.To know the impact of the educational program presentations practical way to develop mental toughness and learn the basic skills for the students in volleyball.The researchers used the experimental program and the research community of the second stage students in the Faculty of Physical Education and Sports Sciences at the University of Babylon for the academic year 2016-2017 (86) students representing the people (B - C - D). The sample of the research was chosen by the random way and represented (24) students after the exclusion of the students and the players of the game and divided into two groups control and experimental, the conclusions were:· There is the impact of the educational program presentations practical way to develop mental toughness basic skills for the students in volleyball.· There is the evolution of the control group in the development of mental toughness basic skills for the students in volleyball.· There is an advantage in the experimental group to develop mental toughness basic skills for the students in volleyball.· The method of practical presentations took into account the individual differences between the students, so the evolution was evident in all the variables.Keywords: Practical presentations, Mental toughness and basic skills.